CIRP Secretion during Cardiopulmonary Bypass Is Associated with Increased Risk of Postoperative Acute Kidney Injury - Liu, Wenyan; Yan, Yang; Han, Dan; Li, Yongxin; Wang, Qian; Li, Jing; Liu, Fengfeng; Zheng, Xinglong (The Thoracic and Cardiovascular Surgeon, 2021)
Background Systemic inflammation contributes to cardiac surgery–associated acute kidney injury (AKI). Cardiomyocytes and other organs experience hypothermia and hypoxia during cardiopulmonary bypass (CPB), which induces the secretion of cold-inducible RNA-binding protein (CIRP). Extracellular CIRP may induce a proinflammatory response.Materials and Methods The serum CIRP levels in 76 patients before and after cardiac surgery were determined to analyze the correlation between CIRP levels and CPB time. The risk factors for AKI after cardiac surgery and the in-hospital outcomes were also analyzed.Results The difference in the levels of CIRP (ΔCIRP) after and before surgery in patients who experienced cardioplegic arrest (CA) was 26-fold higher than those who did not, and 2.7-fold of those who experienced CPB without CA. The ΔCIRP levels were positively correlated with CPB time (r = 0.574, p < 0.001) and cross-clamp time (r = 0.54, p < 0.001). Multivariable analysis indicated that ΔCIRP (odds ratio: 1.003; 95% confidence interval: 1.000–1.006; p = 0.027) was an independent risk factor for postoperative AKI. Patients who underwent aortic dissection surgery had higher levels of CIRP and higher incidence of AKI than other patients. The incidence of AKI and duration of mechanical ventilation in patients whose serum CIRP levels more than 405 pg/mL were significantly higher than those less than 405 pg/mL (65.8 vs. 42.1%, p = 0.038; 23.1 ± 18.2 vs. 13.8 ± 9.2 hours, p = 0.007).Conclusion A large amount of CIRP was released during cardiac surgery. The secreted CIRP was associated with the increased risk of AKI after cardiac surgery.
Keywords: acute kidney injury; CIRP; cardiac surgery; inflammation